Small and in‐country herbaria are vital for accurate plant threat assessments: A case study from Peru - Jay Delves; Joaquina Albán‐Castillo; Asunción Cano; Carmen Fernández Aviles; Edeline Gagnon; Paúl Gonzáles; Sandra Knapp; Blanca León; Jose Luis Marcelo‐Peña; Carlos Reynel; Rocío del Pilar Rojas Gonzáles; Eric F. Rodríguez Rodríguez; et al. (Plants, People, Planet, 2024)
Societal Impact Statement Herbaria can be considered plant libraries, each holding collections of dried specimens documenting plant diversity in space and time. For many plant species, these are our only evidence of their existence and the only means of assessing their conservation status. Specimens in all herbaria, especially those in small and often under‐resourced herbaria in megadiverse countries, are key to achieving accurate estimates of the conservation status of the world's plant species. They are also part of a country's shared heritage and critical contributions to knowledge of the world's diversity. Summary Internationally agreed targets to assess the conservation status of all plant species rely largely on digitised distribution data from specimens held in herbaria. Using taxonomically curated databases of herbarium specimen data for the mega‐diverse genera Begonia (Begoniaceae) and Solanum (Solanaceae) occurring in Peru, we test the value added from including data from local herbaria and herbaria of different sizes on estimations of threat status using International Union for Conservation of Nature (IUCN) Red List criteria. We find that the Global Biodiversity Information Facility (GBIF) has little data from Peruvian herbaria and adding these data influences the estimated threat status of these species, reducing the numbers of Critically Endangered and Vulnerable species in both genera. Similarly, adding data from small‐ and medium‐sized herbaria, whether in‐country or not, also improves the accuracy of threat assessments. [Correction added on 08 September 2023, after first online publication: In the preceding sentence, “litter” has been corrected to “little” in this version.] A renewed focus on resourcing and recognising the contribution of small and in‐country herbaria is required if we are to meet internationally agreed targets for plant conservation. We discuss our case study in the broader context of democratising and increasing participation in global botanical science.